Development of Intratumoral Drug Delivery Based Strategies for Antitumor Therapy - Jiang Z; Fu Y; Shen H (Dove Medical Press, 2024)
Zhimei Jiang,1- 3 Yuzhi Fu,1- 3 Hongxin Shen1- 3 1Department of Pharmacy, West China Second University Hospital of Sichuan University, Chengdu, People's Republic of China; 2Evidence-Based Pharmacy Center, West China Second University Hospital of Sichuan University, Chengdu, People's Republic of China; 3Key Laboratory of Birth Defects and Related Diseases of Women and Children (Sichuan University), Ministry of Education, Chengdu, People's Republic of ChinaCorrespondence: Hongxin Shen, West China Second University Hospital, Sichuan University, No. 20, Third Section, Renmin South Road, Chengdu, Sichuan, 610041, People's Republic of China, Email 1103747222@qq.comAbstract: Research for tumor treatment with significant therapy effects and minimal side-effects has been widely carried over the past few decades. Different drug forms have received a lot of attention. However, systemic biodistribution induces efficacy and safety issues. Intratumoral delivery of agents might overcome these problems because of its abundant tumor accumulation and retention, thereby reducing side effects. Delivering hydrogels, nanoparticles, microneedles, and microspheres drug carriers directly to tumors can realize not only targeted tumor therapy but also low side-effects. Furthermore, intratumoral administration has been integrated with treatment strategies such as chemotherapy, enhancing radiotherapy, immunotherapy, phototherapy, magnetic fluid hyperthermia, and multimodal therapy. Some of these strategies are ongoing clinical trials or applied clinically. However, many barriers hinder it from being an ideal and widely used option, such as decreased drug penetration impeded by collagen fibers of a tumor, drug squeezed out by high density and high pressure, mature intratumoral injection technique. In this review, we systematically discuss intratumoral delivery of different drug carriers and current development of intratumoral therapy strategies. Keywords: intratumoral drug delivery, drug carrier, treatment strategy, antitumor therapy